NLRP3 promotes inflammatory signaling and IL-1β cleavage in acute lung injury caused by cell wall extract of Lactobacillus casei - Lingui Gu; Jinjin Zhu; Qingbing Nie; Binghua Xie; Shuo Xue; Ailing Zhang; Qiangwei Li; Zhengzhong Zhang; Shupeng Li; Yusen Li; Qinquan Shi; Weiwei Shi; et al. (Communications Biology)
Abstract Gram-positive bacterial pneumonia is a significant cause of hospitalization and death. Shortage of a good experimental model and therapeutic targets hinders the cure of acute lung injury (ALI). This study has established a mouse model of ALI using Gram-positive bacteria Lactobacillus casie cell wall extracts (LCWE) and identified the key regulator NLRP3. We show that LCWE induces TNF, NF-κB signaling, and so on pathways. Similar to lipopolysaccharide (LPS), LCWE induces the infiltration of CD11b-positive cells and inflammation in lungs. LCWE also triggers inflammatory signaling through TLR2, different from LPS through TLR4. It suggests that cytokines amplify inflammation signaling relying on NLRP3 in LCWE-induced ALI. NLRP3 deletion disrupts inflammation, IL-1β cleavage, and the infiltration of neutrophils and macrophages in the injured lung. Our study highlights an animal ALI model for Gram-positive bacterial pneumonia and that NLRP3 is a key therapeutic target to prevent inflammation and lung damage in LCWE-induced ALI.